What should I use to calculate vehicle EES? - Moravcová, Pavlína; Bucsuházy, Kateřina; Zůvala, Robert; Semela, Marek; Bradáč, Albert (PUBLIC LIBRARY SCIENCE, 2024)
Comprehensive crash analysis includes calculating impact speed, which requires the determination of kinetic energy expended on the deformation of the vehicle's structural elements at the point of contact during a collision. The accuracy of the input data affects the resulting analysis of the crash. Therefore, this article aims to analyse selected factors influencing the determination of Energy Equivalent Speed (EES) determination using the CRASH3 algorithm: the extent of damage using defined measurement points, deformation width, and also limit speed b0. The variables were varied depending on selected factors such as the extent of damage, the type of collision (overlap), and also vehicle type (vehicle category classification). The presented study concluded that using 2 equally spaced measurement points to define the deformation profile should not be recommended in forensic practice when using CRASH3 algorithm. Using 7 measurement points seems more appropriate in case of equal spacing, even though the differences in calculated EES are not high when using 5 or 6 measurement points, especially with respect to the inaccuracy/technically acceptable tolerance of the EES value determination. The resulting EES is significantly influenced by variation of the deformation width. The used b0 range had a significant effect on the resulting EES value only in the case of SUVs. These vehicles show higher stiffness, which supposes the use of lower b0 values should not be recommended.
Keywords: deformation energy; EES; profile deformation; measurement points; deformation width; CRASH3